Sustainable Growth Rate - A Case Study on Wipro and Infosys - Sam Luther, C. T. (Indian Journal of Finance, 2010)
In the present era of highly competitive environment, companies are striving hard to earn a reasonably good profit to increase the shareholders' wealth. The increase in the wealth of the shareholders depends upon a target profit which can be achieved within a reasonable period of time. Now the question remains- how an investor is let to know how long earnings growth can last. The easy way to gauge such a situation is by calculating the company's sustainable growth rate (SGR).